Building the developmental state: achieving economic growth through co-operative solutions: a comment on bringing politics back in - Huff, W.G.; Oughton, C.; Dewit, G.
Drawing on the insights of game theory and East Asian experience, this short note argues the importance of co-operative solutions in achieving economic development. To realise these, even genuine developmental states must convince a sceptical private sector of their commitment to economic development. Because of this, credibility should be added to the mix of ingredients necessary for a successful developmental state. - Reproduced.
Keywords: Economic growth